Beta-Alanine improves sprint performance in endurance cycling - van Thienen, R.; van Proeyen, K.; van den Eynde, B.; Puype, J.; Lefere, T.; Hespel, P. (Medicine & Science in Sports & Exercise, 2009)
Purpose: Recent research has shown that chronic dietary [beta]-alanine ([beta]ALA) supplementation increases muscle carnosine content, which is associated with better performance in short (1-2 min) maximal exercise. Success in endurance competitions often depends on a final sprint. However, whether [beta]ALA can be ergogenic in sprint performance at the end of an endurance competition is at present unknown. Therefore, we investigated the effect of 8-wk [beta]ALA administration in moderately to well-trained cyclists on sprint performance at the end of a simulated endurance cycling race.